ANALISIS KETERAMPILAN KLASIFIKASI DAN INFERENSI MELALUI PENERAPAN MODEL PROBLEM SOLVING - Novita Safitri; Ila Rosilawati; Nina Kadaritna (Universitas Lampung, 2013)
This research is using for describing classification and inference skills of acid-base material through problem solving model application for student cognitive group in high, medium, and low categories .The subject is 49 students of XI science 4 at 2012/2013 school years in MAN 1 Bandar Lampung. The method for this research is pre-experiment with one shot case study design and descriptive analysis for data analysis. This research will show: (1) classification skill. All student in high category have excellent skill, almost all student have excellent skill and few of them have good skill in medium and low category. (2) inference skill. For high category, almost all of student have excellent skill and few of them have good skill. for medium category, few student have intermediate skill and for low category few student have excellent skill, a half more have good and intermediate skill and for other few student have poor skill. High category is better in classification and inference skills than medium and low category.Kata Kunci : problem solving, klasifikasi, inferensi, kelompok tinggi, kelompok sedang, kelompok rendah